Designing a Sound Programming Kit for Elementary School Students - Putra, Taufiq Pratama; Junaeti, Enjun; Sutarno, Heri (Jurnal Guru Komputer, 2022)
The development of technology and knowledge is currently being updated. The generation born and accustomed to the digital world in his life is known as "digital natives". Elementary school age children are classified as "digital natives" and they should be directed to have technological expertise. One way to make these "digital natives" productive is to introduce the basic concepts of programming and electronics from an early age by using a sound programming kit. The design of this sound programming kit pays attention to the characteristics of elementary school students. This kit uses Arduino as a platform to run this kit because Arduino devices are easy to obtain, cost-effective, thus Arduino is recommended to introduce algorithms and programming for elementary school students. This study uses the ADDIE research method with the participants of teachers Miftahul Iman Elementary School Bandung. From this study the results obtained are 1) the sound programming kit that had been developed through several stages, namely analysis, design, development, implementation, and evaluation is rated “Very Good” by media experts with an average percentage of eligibility of 88.95%, 2) The teacher who did the test obtained an average Pretest score of 38.3 and an average Post-test score of 83.3, therefore gaining an increased value by 45. 3) The sound programming can be an alternative learning medium for teachers because it is interesting to be done by students and very flexible because it can be done outside of school.